2013
DOI: 10.1007/s00442-013-2795-4
|View full text |Cite
|
Sign up to set email alerts
|

Major consequences of minor damage: impacts of small grazers on fast-growing kelps

Abstract: Damage by small herbivores can have disproportionately large effects on the fitness of individual plants if damage is concentrated on valuable tissues or on select individuals within a population. In marine systems, the impact of tissue loss on the growth rates of habitat-forming algae is poorly understood. We quantified the grazing damage by an isopod Amphoroidea typa on two species of large kelps, Lessonia spicata and Macrocystis pyrifera, in temperate Chile to test whether non-lethal grazing damage could re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…These have provided reasonable coverage of the intertidal and shallow subtidal diversity of coral reef, seagrass, and mangrove habitats and of benthic species of fish, molluscs, crustaceans, and larger echinoderms of current or potential commercial interest. A similar pattern of knowledge is found for other groups with reasonable knowledge of intertidal and shallow biodiversity declining rapidly as one moves offshore [20,21]. We suggest that even in the relatively well-known groups of fish, molluscs, crustaceans, and larger echinoderms, biodiversity has been seriously underestimated and certainly the numbers of undescribed species increases with depth and distance from the coast.…”
Section: Exceptional High Biodiversity Of the Indo-pacific Regionsupporting
confidence: 78%
“…These have provided reasonable coverage of the intertidal and shallow subtidal diversity of coral reef, seagrass, and mangrove habitats and of benthic species of fish, molluscs, crustaceans, and larger echinoderms of current or potential commercial interest. A similar pattern of knowledge is found for other groups with reasonable knowledge of intertidal and shallow biodiversity declining rapidly as one moves offshore [20,21]. We suggest that even in the relatively well-known groups of fish, molluscs, crustaceans, and larger echinoderms, biodiversity has been seriously underestimated and certainly the numbers of undescribed species increases with depth and distance from the coast.…”
Section: Exceptional High Biodiversity Of the Indo-pacific Regionsupporting
confidence: 78%
“…mollusks and echinoderms) increased the abundance of early stages of kelp Macrocystis pyrifera in comparison to treatments with low densities and/or total exclusion of herbivores (Henríquez et al 2011). Two reasons could explain this pattern: (1) the strong consequences of grazer abundance and identity on the intertidal landscape (see Poore et al 2012Poore et al , 2014 and (2) some biogenic habitats (e.g. calcareous algae, empty limpet shells) can provide protection from severe grazing for sporelings of macroalgae (see Camus 1994, Henríquez et al 2011.…”
Section: Effect Of Grazers On Spatial Patterns Of L Berteroana Recrumentioning
confidence: 95%
“…Depending on the availability of food, foraging strategies, identity and abundance of grazers, and exploitation intensity, primary producer stands can change their spatial and temporal patterns of distribution (Adler et al 2001, Duffy 2002, Steneck et al 2013, Poore et al 2014. Herbivory influences both intra-and interspecific relationships in local communities and modifies the landscape structure (Duffy 2002, Poore et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In seagrass communities, Ebrahim et al (2014) found exclusion of mesograzers resulted in a 233% increase in epiphyte biomass, which many associate with declines in seagrass abundance (Orth and Van Montfrans, 1984). In kelp forest communities, mesograzers can also strongly affect aquatic plants; Poore et al (2014) found that while non-lethal, small isopod grazers can reduce kelp blade growth by 80%. Given the importance of mesograzers in other ecosystems, it is important to revisit their role in regulating coral reef macroalgal communities, particularly under reduced herbivore abundance and increased nutrient conditions.…”
Section: Discussionmentioning
confidence: 96%